L. N. Gumilev. La búsqueda de un reino imaginario; la leyenda del preste Juan. Prólogo de Josep Fontana. Barcelona: Crítica, Grupo Grijalbo-Mondadori, 1994. xii+467 pp. - Hernán Taboada (El Colegio de México, A.C., 1998)
-